2022
DOI: 10.3390/nano12050885
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization and Antibacterial Properties of Carbon Dots from Two Mediterranean Olive Solid Waste Cultivars

Abstract: Carbon nanomaterials have shown great potential in several fields, including biosensing, bioimaging, drug delivery, energy, catalysis, diagnostics, and nanomedicine. Recently, a new class of carbon nanomaterials, carbon dots (CDs), have attracted much attention due to their easy and inexpensive synthesis from a wide range of precursors and fascinating physical, chemical, and biological properties. In this work we have developed CDs derived from olive solid wastes of two Mediterranean regions, Puglia (CDs_P) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The antibacterial activity and mechanism are affected by several factors including CND physiochemical properties such as their sizes, surface charges, and the nature of surface defects and functional groups . Various previous reports showed that the carboxylated carbon nanotubes and graphene oxide nanomaterials exhibit broad-spectrum antimicrobial activity through the oxidative stress which leads to bacterial cell death. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The antibacterial activity and mechanism are affected by several factors including CND physiochemical properties such as their sizes, surface charges, and the nature of surface defects and functional groups . Various previous reports showed that the carboxylated carbon nanotubes and graphene oxide nanomaterials exhibit broad-spectrum antimicrobial activity through the oxidative stress which leads to bacterial cell death. …”
Section: Resultsmentioning
confidence: 99%
“…The different response of the various bacterial strains tested to CNDs could be ascribed to their cellular membrane nature and composition …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations